Removal of CI Basic Blue 41 from aqueous solution by supercritical water oxidation in continuous-flow reactor - Sogut, Onur O.; Akgun, Mesut (ELSEVIER SCIENCE INC, 2009)
Oxidation of aqueous solution of C.I. Basic Blue 41 (BB41), which is model azo dye pollutants, was studied in a continuous-flow reactor that was operated between 400 and 650 degrees C at a fixed pressure of 25 MPa. The total organic carbon (TOC) concentration of BB41 was in the range of 30.60 and 152.97 mmol/L in the feed stock solution. Hydrogen peroxide (H2O2) was used as an oxygen source and the oxidant concentrations were between 73.53 and 489.64 mmol/L in the feed stock solution. The results demonstrated that supercritical water oxidation (SCWO) process decreases the TOC up to 99.87% in very short reaction times (at residence times of 9-19 s). According to the wastewater and oxidant concentrations, the global rate expression was regressed from the complete set of data for each dye solution. As a result of regression analysis, the reaction rate expression for the oxidation of BB41 was determined with the activation energy of 18.88 (+/- 0.9) kJ/mol and the pre-exponential factor of 2.8 (+/- 0.5) mmol(-0.16) L-0.16 s(-1); and the reaction orders for BB41 (based on TOC) and the oxidant were 0.84 (+/- 0.03) and 0.32 (+/- 0.05) in a 95% confidence level. (C) 2009 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.
Keywords: Supercritical water oxidation; Textile wastewater; Basic Blue 41; Total organic carbon; CATALYTIC WET OXIDATION; WASTE-WATER; AZO-DYE; AIR OXIDATION; DEGRADATION; DECOLORIZATION; DECOMPOSITION; KINETICS; OZONE; Chemistry; Engineering